Adherence to statins and the risk of psoriasis: a population‐based cohort study. (12th June 2015) - Chodick, G.; Weitzman, D.; Shalev, V.; Weil, C.; Amital, H.
Summary: Background: Statins have been shown to downregulate immune mechanisms activated in psoriasis. However, previous studies on their potential role in preventing psoriasis have yielded conflicting results. Objectives: To assess the relationship between adherence to statins and the risk of psoriasis. Methods: This retrospective cohort study included 205 820 health plan enrollees in Israel (mean age 55 years; 54·1% women) who initiated statin treatment from January 1998 through to September 2009. Adherence to statins, measured by the proportion of days covered (PDC), throughout the entire follow‐up period (mean 6·2 years) was recorded. Diagnosis codes of psoriasis were assigned by a dermatologist or rheumatologist, or at discharge from hospital. Results: During 1·28 million person‐years (PY) of follow‐up (median 5·74 years per person; interquartile range 3·78–8·36), 5615 cases of psoriasis (incidence density rate 4·4 per 1000 PY) were recorded. Compared with patients who did not adhere to statins (PDC < 20%), patients covered by statins for 40–59% of the time had a significantly lower risk of psoriasis ( P  < 0·05), with hazard ratios (HRs) of 0·84 and 0·74 among men and women, respectively. Among patients who adhered better to statins (PDC ≥ 80%), HRs were 0·88 (95% CI 0·79–0·98) and 1·00 (95% CI 0·90–1·11) among men and women, respectively. Conclusions: The results of the current study suggest that high and long‐term adherence to statins is not associated with a meaningful reduction in the risk of developing psoriasis. Abstract : What's already known about this topic? In addition to their potent cholesterol‐lowering properties, statins exert multiple anti‐inflammatory effects that might be relevant for the prevention of psoriasis. The results of the few previous epidemiological studies of statin use and psoriasis are conflicting. What does this study add? In this large observational study, long‐term adherence to statins was not associated with a lower risk of psoriasis. The results shed new light on the nature of the relationship between statins and the risk of psoriasis.